Irrigation potential based on crop water requirement and time scheduling for spinach grown in cocopeat - Saroni, Nurul Sahirah (2018)
Water is a major issue in agriculture because of limited water sources. Over or excessive irrigation of water to plants will affect plant respiration as the roots cannot take in gases. On the contrary, shortage of water due to under irrigation will lead to water stress. By knowing the actual crop water requirement and time scheduling irrigation, plant damage can be reduced and thus, yield and cost efficiency can increase. Spinach is one of the leafy vegetable that is very sensitive to water. Small changes in water application to spinach can be detected from its growth performance. Thus, an irrigation potential was affected by different amount of water application on spinach to observe its growth. The objective of this experiment was to determine the actual amount of water required for spinach grown in cocopeat based on crop water requirement and time scheduling in order to avoid over or under irrigation. This study was conducted in the shade house, Field 15 at Faculty Agriculture, UPM. There were three treatments of irrigation tested, common irrigation practice, crop water requirement irrigation and time scheduling irrigation. The experimental design for this experiment was RCBD with 4 blocks (replications) for each treatment and each experimental plot had 10 spinach plants. CROPWAT 8.0 software was used to calculate reference evapotranspiration for the determination of crop water requirement. Data collections include plant height, leaf length, and number of leaves, root length, canopy diameter and fresh weight of the spinach. The effect of irrigation on these spinach performances was analyzed with Statistically Analysis System (SAS). The result for this study showed no significant difference among the treatments for all the growth parameters tested except for plant height at 14 days after transplanting. The insignificant difference was hypothesized to be contributed by that cocopeat medium used in this study that had provided satisfactory available water for the spinach growth regardless different amounts of irrigation water applied.